Consistent and effective energy utilisation of node model for securing data in wireless sensor networks. (2018) - Balamurugan, P.; Karuppiah, Marimuthu; Mummoorthy, A.; Viswabharathi, A.M.; Niranchana, R.
This paper introduces the new routing model called Effective Energy Utilisation of Node Model (EEUNM) created for energy-efficient and secure data in wireless sensor networks. EEUNM deals with wireless sensor applications such as military and forest field. The aim of this model is to find the perfect path based on consumption of node energy. The focus of EEUNM is a new approach to simultaneously factor energy and trustworthiness of routes in the routing model. EEUNM finds and selects the path on the basis of having maximum capability of node with incurring additional cost in overhead compared to the common protocols AODV-EHA and LTB-AODV. In this work, simulation results show that the proposed model EEUNM keeps the same security level while completing better energy utilisation of nodes for data packet delivery.